The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12894-018-0370-3
|View full text |Cite
|
Sign up to set email alerts
|

The location of the bladder neck in postoperative cystography predicts continence convalescence after radical prostatectomy

Abstract: BackgroundThis study was conducted to determine whether the location of the bladder neck in postoperative cystography predicts recovery of continence after radical prostatectomy.MethodsBetween 2008 and 2015, 203 patients who underwent laparoscopic radical prostatectomy (LRP, n = 99) and robot assisted radical prostatectomy (RARP, n = 104) were analyzed. The location of the bladder neck was visualized by postoperative routine cystography, and quantitative evaluation of the bladder neck position was performed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Postoperative cystography is a useful tool for predicting post-prostatectomy incontinence. A higher vesico-urethral anastomosis location is associated with a higher rate of early recovery of UC, and a wider bladder neck angle is associated with a high rate of early recovery of UC (12)(13)(14)(15)(16). Our data also demonstrated that early recovery of UC was observed in patients with wider bladder neck angle, however the postoperative location of bladder neck did not show any significant association with early recover of UC after NNS-LRP in multivariate analysis.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Postoperative cystography is a useful tool for predicting post-prostatectomy incontinence. A higher vesico-urethral anastomosis location is associated with a higher rate of early recovery of UC, and a wider bladder neck angle is associated with a high rate of early recovery of UC (12)(13)(14)(15)(16). Our data also demonstrated that early recovery of UC was observed in patients with wider bladder neck angle, however the postoperative location of bladder neck did not show any significant association with early recover of UC after NNS-LRP in multivariate analysis.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have reported several factors associated with postoperative UI: i) demographic factors, including age, prostate volume, prostatic apical shape, membranous urethral length and preoperative lower urinary tract symptoms (LUTS) (3)(4)(5)(6)(7)(8), ii) surgical technique-related factors, including posterior and anterior wall reconstruction, nerve sparing procedure, and bladder neck preservation, which are potentially related to the early recovery of postoperative urinary continence (UC) (9)(10)(11). In addition to preoperative and intraoperative factors, postoperative findings, such as cystography suggested to be a reliable tool for predicting postoperative UI (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A unique aspect of the present study was that the BNAP ratio was associated with early continence recovery after RARP. In previous studies, postoperative cystography parameters were only measured in the coronal view of cystography [9,10,[12][13][14]16]. However, I anticipated that the force transmission of urine from the bladder neck to the urethra could be three-dimensional rather than two-dimensional.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similar results were reported by other authors confirming the role of bladder neck to pubic symphysis ratio to predict urinary continence recovery following RP. 15,16 In 2015, Shao et al 5 showed that relative position of bladder neck to pubic symphysis and bladder neck angle were stronger predictors of urinary continence recovery. More recently, Huh et al 6 identified bladder neck elevation as a predictor of urinary continence after RARP.…”
Section: Discussionmentioning
confidence: 99%